Fattening and meat qualities of young pigs of different intrabreed differentiations by origin and breeding value - Khalak, Viktor; Халак, Віктор Іванович; Horchanok, Anna; Horchanok, A.; Horchanok, A. V.; Горчанок, Анна Володимирівна; Lytvyschenko, L.; Litvischenko, L. O.; Litvischenko, Lіudmyla; Lytvyschenko, L. O.; Lytvyshchenko, L.; Lytvyschenko, Lyudmila; et al. (University of Agronomic Sciences and Veterinary Medicine of Bucharest, Romania – Faculty of Animal Science Engineering and Management, 2022)
The paper presents the results of the study on fattening and meat qualities of young pigs of different intrabreed differentiation by origin and breeding value. The research was conducted on farms and processing enterprises of Dnipropetrovsk region, as well as in the Laboratory of Animal Husbandry of the State Institution "Institute of Grain Crops of NAAS of Ukraine". It was established that Large White young pigs from the controlled population at the age of achievement of live weight in 100 kg, at the fatback thickness at the level of 6-7 thoracic vertebrae and at the length of the chilled carcass exceed the minimum requirements of the elite class by 13.85% in average. Significant differences between animals of English and Hungarian origin were established in the average daily gain of live weight (2.28%) and the age of achievement of live weight in 100 kg (3.58%). Young pigs from group I (intrabreed differentiation by selection index "И") and from group II (intrabreed differentiation by Sazer-Fredin index) exceeded peers from opposite groups in the average daily gain in live weight by 7.48-2.75%; in the age of achievement of live weight in 100 kg by 3.87-3.41%. The difference between the groups in the fatback thickness at the level of 6-7 thoracic vertebrae, in the length of the chilled carcass and in the length of the bacon side of the chilled carcass varied from 0.51 to 12.16%. The maximum increase in additional products was obtained from the sale of one head of Large White young pigs of English origin (+1.86%), animals from group I of intrabreed differentiation by selection index "И" (+3.39%) and animals from group II of intrabreed differentiation by index Sazer-Fredin (+2.11%). Based on the obtained data, it was established that the criterion for selection of highly productive animals is the value of the selection index "И" +0.181 - +3.205, Sazer-Fredin index -1.017 - -0.102. У статті наведено результати дослідження відгодівельних і м’ясних якостей молодняку свиней різних внутрішньопорідних груп. диференціація за походженням і племінною цінністю. Дослідження проводились на фермах та переробних підприємствах Дніпропетровської області, а також в лабораторії тваринництва ДУ «Інститут зернових культур НААН України». Встановлено, що молодняк великої білої породи з контрольованого поголів'я у віці досягнення живої маси 100 кг, при товщині сала на рівні 6–7 грудних хребців і при довжині охолоджена тушка перевищує мінімальні вимоги класу еліта в середньому на 13,85%. Істотні відмінності між тваринами англійського та угорського походження встановлено середньодобовий приріст живої маси (2,28%) та вік досягнення живої маси в 100 кг (3,58%). Молодняк I групи (внутрішньопородна диференціація за селекційний індекс «І») і з ІІ групи (внутрішньопородна диференціація за індексом Сазера-Фредіна) перевищували однолітків з протилежної групи в середньодобовому прирості живої маси на 7,48-2,75%; у віці досягнення живої маси 100 кг 3,87–3,41%. Різниця між групами в товщині жиру на рівні 6-7 грудних хребців, у довжини охолодженої туші і довжини беконної сторони охолодженої туші коливалася від 0,51 до 12,16%. Максимальний приріст додаткової продукції отримано від реалізації однієї голови молодняку великої білої породи англійського походження (+1,86%), тварини І групи внутрішньопородної диференціації за селекційним індексом «І» (+3,39%) та тварин ІІ групи внутрішньопородної диференціації за індексом Сазера-Фредіна (+2,11%). Виходячи з отриманих даних було встановлено, що критерієм відбору високопродуктивних тварин є значення селекційного індексу «И» +0,181 – +3,205, індекс Сазера-Фредіна -1,017 – -0,102.
Відгодівельні і м’ясні якості молодняку свиней великої білої породи різних генеалогічних ліній та економічна ефективність їх використання
Горчанок Анна Володимирівна https://orcid.org/0000-0003-0103-1477 Литвищенко Людмила Олександрівна http://orcid.org/0000-0002-4239-5405
Keywords: young pigs; молодняк свиней; breed; порода; correlation; співвідношення; economic efficiency; економічна ефективність; fattening and meat qualities; відгодівельні та м’ясні якості; index; індекс; variability; мінливість